Self-Esteem, Optimism and Burden of Care among Relatives of Cardiovascular Disease Patients in Selected Tertiary Hospitals in Southwest, Nigeria - Babatunde, Stephen Ishola; Bankole, Taofik Olatunji; Yinusa, Rasheed Adebayo (Journal of Diseases, 2019)
Providing informal care, particularly for a person needing assistance for daily activities as a result of chronic illness such as cardiovascular disease (CVD), is a demanding task which requires time, dedication and preservation. In spite of burdens that caregivers of CDV patients are faced with, there are dearth of studies that have explored the level of the burden of care among relatives of CVD in Nigeria. This study addresses this gap by raising the question: to what extent does care for CVD patients affect caregiver’s psychological, behavioral and physiological daily lives. The study was a cross-sectional survey and it adopted the purposive sampling technique. Primary data were sourced from 200 caregivers/relatives from three tertiary hospital: Federal Teaching Hospital Ido-Ekiti, Federal Medical Centre Owo and Obafemi Awolowo Teaching Hospital Complex Ile-Ife. The outcome variable is caregiver’s burden, and the key explanatory variables are self-esteem and optimism. The Zarit (ZBIS), Rosenburg Self Esteem and Revised Life Orientation Test (LOT-R) standardised psychological scales were employed to measure caregiver’s burden, self-esteem and optimism. Pearson r was applied using Stata version 13. Results showed that a significant proportion of the caregivers experienced moderate to severe levels of burden. Also, results showed that caregivers’ burden was not significantly associated with Self-esteem (r200 = 0.04, p >.025) and optimism (r200 = 0.07, p >.025). It was imperative to provide professional help and supportive counselling to caregivers of CVD patients, in order to reduce their burden, strengthen the coping skill and thus improve their quality of life.